Shared space: Negotiating sites of (un)sustainable mobility. Issue 127 (December 2021) - Barr, Stewart; Lampkin, Sal; Dawkins, Laura; Williamson, Daniel
Highlights: Shared mobility spaces need to be understood as complex sites of practice. These spaces often present partial and dysfunctional approaches to sharing space. In the UK, shared mobility spaces represent limiting approaches for promoting sustainable mobility. Researchers need to question whether shared spaces promote sustainability. Abstract: Shared mobility spaces have become increasingly popular internationally as attempts to increase the uptake of active travel modes (walking, cycling and running) have turned pavements, shopping streets and public spaces into multi-mode mobility spaces. From a sustainability perspective, policy makers in the UK have argued that shared spaces afford greater opportunities for cycling off-road in areas with busy traffic, whilst in public spaces they provide greater accessibility and connectivity to a wider range of users. Yet there has been little conceptual critique and empirical research on the impacts of how individuals and groups negotiate what are new forms of public space in the UK. Accordingly, in this paper we use insights from the new mobilities paradigm and social practice theories to analyse data gathered from qualitative research with different travel mode users in the city of Exeter (South-west England) to demonstrate the complexity of shared spaces, the tensions they produce and the challenges they may pose for promoting sustainable mobility. First, we explore the practices that unfold within shared spaces and demonstrate how researchers need to appreciate the social complexity of negotiating new and conflictual sites of practice. Second, we examine how a fragmented approach to the design of shared spaces may compromise the development of sustainable mobility practices through representing a partial and dysfunctional approach towards sharing space in cities. Third, we demonstrate the problematics of deploying shared spaces as short-term and politically expedient devices for delivering individually-focused behavioural goals instead of radical alternatives that embed sustainable mobility infrastructure into urban fabrics. We conclude by suggesting that to realise the benefits of collectively sharing mobility space in the UK requires long-term changes in urban infrastructure that can embed practices and promote a shift away from the political dominance of the private vehicle as the axis around which urban development pivots.